Buffalo Bull Fertility: Key Factors and Predictive Markers - Kumar, Sushil; Biswas, Newton; Ghosh, S K; Srivastava , Neeraj (Animal Reproduction Update, 2025)
Buffalo bull fertility is pivotal to reproductive success and genetic improvement in  the dairy sector, especially in regions with high buffalo populations such as India.  Despite their economic importance, reproductive inefficiencies, most notably  low conception rates after artificial insemination, remain major challenges. Male  fertility is a complex trait influenced by sperm quality, seminal plasma composition,  hormonal and biochemical profiles, genetic determinants, and environmental factors.  Key functional markers associated with high fertility include elevated sperm motility  (total 77.6%, progressive 73.73%), membrane and acrosome integrity (74.17% and  92.83%, respectively) in fertile bulls versus significantly lower values in sub-fertile  animals. Important seminal plasma biochemical markers such as follicle-stimulating  hormone (FSH), luteinizing hormone (LH), testosterone, insulin-like growth factor-1  (IGF-1) are all higher in fertile buffalo bulls, for example, LH at 0.28 ± 0.02 mU/ mL and testosterone at 0.53 ± 0.02 ng/mL in fertile animals. Fertile bulls also show  superior antioxidant capacity (TAC, catalase, glutathione peroxidase, and nitric  oxide) and lower oxidative stress marker malondialdehyde (MDA). Proteomic studies  have identified differentially abundant sperm proteins such as AKAP3, AKAP4,  Sp17, and PDIA3 (upregulated in high fertility) while DLD is downregulated, all  strongly linked to sperm motility, structural integrity, and zona pellucida binding.  Transcriptomic profiling further highlights up-regulated hub genes (e.g., RPL36AL,  EIF5A, RPLP0) as promising molecular markers for sperm quality and fertility  assessment. Integrating conventional semen analysis with molecular technologies,  including omics-based biomarker identification, offers improved accuracy in fertility  prediction and supports effective selection of breeding bulls. These strategies are  essential for optimizing reproductive outcomes, minimizing economic losses, and  advancing sustainable buffalo productivity.
Keywords: Artificial insemination efficiency; Buffalo bull fertility; Semen quality; Seminal plasma biomarkers; Proteomics and transcriptomics